Islamic Modernism and Tafsir in Nineteenth Century Egypt: A Critical Analysis of Muhammad Abduh’s Exegesis - Adam, Ibrahim Ilyasu (Journal of Quranic Sciences and Research, 2023)
The aim of this paper is to examine the concept of Islamic modernism in nineteenth-century Egypt as expressed in Tafsir al-Manar, placing particular emphasis on Muhammad ‘Abduh (1849-1905). The major focus of the paper is human reason (‘aql) as perceived by ‘Abduh and reflected in Tafsir al-Manar.  Towards the end of the nineteenth century, Quranic exegesis gained new momentum with the emergence of Islamic modernism. In Egypt, ‘Abduh used tafsir as a major vehicle to disseminate his revolutionary thoughts. The central concept of his reform was that Islam could not face the challenges of modernity and the West unless Muslims learnt modern and other rational sciences. ‘Abduh abandoned the traditional formula of tafsir in favour of the rationalist approach, which he believed was essential in order to demonstrate the viability of Islam to the modern period.  Traditional exegetes, he argued, had wasted too much effort on delving into the ‘technicalities’ of grammar, theological disputes and other extraneous material. Tafsir, he maintained, had to be presented in a style adaptable to the demands of the society. Moreover, for the present situation of Muslims to be improved and for Islamic modernism to be sustained, the Quran had to be rationally interpreted.  This paper examines the concept of Islamic modernism in nineteenth century Egypt, as expressed in Tafsir al-Manar, making particular reference to Muhammad ‘Abduh (1849-1905).   It evaluates his contributions to modern tafsir and analyse his rational approach in the interpretation of the Quran.